It is the habit not the handle that affects tooth brushing - a randomised counterbalanced cross over study with young and healthy adults - Renate Deinzer; Zdenka Eidenhardt; Keywan Sohrabi; Manuel Stenger; Dominik Kraft; Bernhard Sick; Franz Götz-Hahn; Carlotta Bottenbruch; Nils Berneburg; Ulrike Weik (BMC, 2024)
Abstract Objective To assess the effect of the toothbrush handle on video-observed toothbrushing behaviour and toothbrushing effectiveness. Methods This is a randomized counterbalanced cross-over study. N = 50 university students and employees brushed their teeth at two occasions, one week apart, using either a commercial ergonomically designed manual toothbrush (MT) or Brushalyze V1 (BV1), a manual toothbrush with a thick cylindrical handle without any specific ergonomic features. Brushing behaviour was video-analysed. Plaque was assessed at the second occasion immediately after brushing. Participants also rated their self-perceived oral cleanliness and directly compared the two brushes regarding their handling and compared them to the brushed they used at home. Results The study participants found the BV1 significantly more cumbersome than the M1 or their brush at home. (p < 0.05). However, correlation analyses revealed a strong consistency of brushing behavior with the two brushes (0.71 < r < 0.91). Means differed only slightly (all d < 0.36). These differences became statistically significant only for the brushing time at inner surfaces (d = 0.31 p = 0.03) and horizontal movements at inner surfaces (d = 0.35, p = 0.02). Plaque levels at the gingival margins did not differ while slightly more plaque persisted at the more coronal aspects of the crown after brushing with BV1 (d = 0.592; p 0.042). Discussion The results of the study indicate that the brushing handle does not play a major role in brushing behavior or brushing effectiveness.